(1178) المناهج التحليلية للتضخم – دراسة تطبيقية على الاقتصاد المصرى خلال الفترة من (64/1965 – 1974) Analytical approaches to inflation – an applied study on the Egyptian economy during the period (1964/1965 – 1974) - احمد عبد العزيز الشرقاوي (معهد التخطيط القومي, 2026)
تتناول الدراسة تحليلاً كمياً لظاهرة التضخم في الاقتصاد المصري خلال الفترة من 1964/65 إلى 1974. توضح المذكرة أن التضخم في مصر ليس مجرد ظاهرة نقدية عابرة، بل هو نتاج اختلالات هيكلية عميقة في قطاعات الإنتاج والتوزيع والتمويل. واستخدم الباحث مؤشرات دقيقة مثل "فائض الطلب المحلي" و"فائض المعروض النقدي" ليثبت أن الاقتصاد المصري عانى من ضغوط تضخمية متصاعدة وصلت إلى حد "التفجر" في سنوات ما بعد حرب أكتوبر 1973، نتيجة التوسع في سياسة التمويل بالعجز لمواجهة أعباء الدفاع الوطني وإعادة الإعمار، مما أدى إلى زيادة السيولة بمعدلات تفوق بكثير النمو الحقيقي في الناتج المحلي. كما تستعرض الأسباب الجذرية لهذه المشكلة ضمن أربع مجموعات رئيسية، تشمل الانفجار السكاني وارتفاع الميل للاستهلاك، وغياب استراتيجية تنموية واضحة، وعدم كفاءة السياسات المالية والنقدية، بالإضافة إلى الخسائر الاقتصادية الضخمة الناجمة عن الحروب. وتخلص النتائج إلى أن علاج التضخم يتطلب رؤية شاملة تتجاوز مجرد "تعليق" المسؤولية على الأسعار العالمية أو زيادة بند الإعانات في الموازنة؛ حيث توصي المذكرة بضرورة ربط الأجور بالإنتاجية، وترشيد الإنفاق العام، وتصحيح الاختلالات في توزيع الدخول لضمان الاستقرار الاجتماعي والحد من الارتفاع الجنوني في تكاليف المعيشة التي أرهقت أصحاب الدخول الثابتة This study provides a quantitative analysis of inflation in the Egyptian economy from 1964/65 to 1974. The report demonstrates that inflation in Egypt is not merely a transient monetary phenomenon, but rather the product of deep structural imbalances in the production, distribution, and finance sectors. The researcher uses precise indicators such as "excess domestic demand" and "excess money supply" to prove that the Egyptian economy suffered from escalating inflationary pressures that reached a boiling point in the years following the October 1973 war. This was a result of expanding deficit financing policies to meet the burdens of national defense and reconstruction, leading to an increase in liquidity at rates far exceeding real GDP growth. The study also examines the root causes of this problem within four main categories: population explosion and high propensity to consume, the absence of a clear development strategy, the inefficiency of fiscal and monetary policies, and the enormous economic losses resulting from wars. The findings conclude that addressing inflation requires a comprehensive vision that goes beyond simply attributing responsibility to global prices or increasing subsidies in the budget. The memorandum recommends linking wages to productivity, rationalizing public spending, and correcting imbalances in income distribution to ensure social stability and curb the exorbitant rise in the cost of living that has burdened those with fixed incomes.